1998
DOI: 10.1007/s004020050242
|View full text |Cite
|
Sign up to set email alerts
|

Callus formation in the humerus compared with the femur and tibia during limb lengthening

Abstract: We investigated whether the callus formation in the humerus during the distraction period of limb lengthening proceeds at a higher rate than that in the femur and tibia. Ten achondroplastic patients underwent 3 bilateral humerus, 3 bilateral femur and 4 bilateral tibia lengthenings. To reduce the confounding effect of bone size, we used bone mineral apparent density (BMAD) to compare the three groups; this is a volumetric bone mineral density measurement. BMAD in the distracted callus space was evaluated at 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Complications using monolateral fixators in humeral lengthening are less than for other long bones (Tanaka et al 1998, Hosny 2005, Shadi and Koczewski 2007, Kim et al 2012). Also, when compared with other lengthening devices, the complication rates appear to be lower with monolateral fixators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications using monolateral fixators in humeral lengthening are less than for other long bones (Tanaka et al 1998, Hosny 2005, Shadi and Koczewski 2007, Kim et al 2012). Also, when compared with other lengthening devices, the complication rates appear to be lower with monolateral fixators.…”
Section: Discussionmentioning
confidence: 99%
“…Gradual distraction osteogenesis using either monolateral fixators or circular fixators is the preferred treatment for humeral lengthening and correction of deformity (Cattaneo et al 1990, Tanaka et al 1998, Kashiwagi et al 2001, Lee et al 2005, Kiss et al 2008). However, circular fixators are bulky and difficult to apply, especially bilaterally.…”
mentioning
confidence: 99%
“…This is because callus formation in the humerus during distraction proceeds at a higher rate than in the femur. Tanaka et al 5 reported that there was no significant difference in callus formation in the humerus and femur at eight weeks. We found that the mean PVR of the femur was similar to that of the humerus up to 20 weeks, but showed a significant difference after 20 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…Many authors reported a higher rate of bone formation during distraction of the humerus [20, 21]. The healing index was 29.1 cm (range 22–35 days) after lengthening in 10 patients with achondroplasia who had no complications or sequelae [19].…”
Section: Discussionmentioning
confidence: 99%